Acute Abdomen During Pregnancy - Augustin, Goran (Springer International Publishing, 2018)
This is the second edition of a well-received book that reflects the state of the art in diagnosis and treatment of acute abdominal disorders in the pregnant patient. It addresses a wide range of conditions, whether associated with or incidental to pregnancy, ranging from very rare to more common ones, such as acute appendicitis and acute cholecystitis. It offers an update on recommendations, guidelines and scenarios to provide fundamental support for all clinicians who might encounter such cases. The book highlights the importance of a rapid diagnosis to avoid serious consequences for both the mother and the fetus. Furthermore, it sheds light on the different imaging modalities of rare pathologies that can occur during pregnancy, helping clinicians and radiologists to better define underlying cases. This new edition has been almost completely rewritten, and includes an additional section focusing on urologic emergencies, preterm labor and intra-abdominal pressure, as well as new figures and tables. It is equally valuable for general and abdominal surgeons, gynecologists and obstetricians, as well as emergency physicians, who may be the first specialists to have clinical contact with this group of patients. From the reviews of the first edition: "This book contains most of the information needed to address the problem of acute abdomen in pregnancy and brings state of the art principles and practice of emergency, abdominal surgery, obstetrics, gynecology and maternal-fetal medicine. The book should prompt clinicians, primarily surgeons and obstetricians to make faster and more precise diagnosis, earlier surgical interventions with the optimal outcome for the mother and child, by a multidisciplinary approach." (Translation into English; Original review: Prof. Dr. Tomislav Luetić, Lijec Vjesn, Vol. 137 (5-6), May-June, 2015) "This book provides a detailed description of the various clinical scenarios in which we encounter acute abdominal conditions in pregnant patients. ... This is an excellent resource for practicing acute care surgeons and obstetricians/gynecologists who are most likely to encounter these patients. It also is a very useful resource for general practitioners, since they frequently are the first healthcare professionals who encounter pregnant patients with these conditions." (Prashant Khullar, Doody's Book Reviews, February, 2015).